Pengaruh Live Streaming, Tanggal Kembar dan Media Sosial Terhadap Impulse Buying Gen Z Pada E-commerce Shopee - Nurjanah Nurjanah; Nurul Ikhfa; Ade Fadillah FW Pospos (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2025)
Shopee is an online shopping application. The Shopee application in Indonesia is currently experiencing very rapid development, especially with the emergence of attractive features and targeting younger generation consumers. This study aims to analyze the extent of the influence of live streaming, twin dates and social media on impulse buying gen z on e-commerce Shopee. The methodology used is quantitative and the instruments used are primary data using questionnaires/surveys that process data using SPSS 22. The research sample amounted to 100 respondents. The results of the study show that the live streaming variable obtained a calculated t value (6.080) > t table (1.984) and a significance of 0.000 < 0.05, the twin date variable obtained a calculated t value (-0.474) < t table (1.984) and a significance of 0.636 > 0.05, the social media variable obtained a calculated t value (1.827) < t table (1.984) and a significance of 0.071 < 0.05, Fcount (40.401) > Ftable (3.09) with a significance of 0.000 < alpha (0.05). Thus, the independent variables (Live streaming, Double Date, and Social Media) simultaneously have a significant effect on Impulse buying among Gen Z on Shopee E-commerce. It can be concluded that the hypothesis is accepted. The result of the Coefficient of Determination (R²) test shows an adjusted R² value of 0.544. This means that 54.4% of Impulse buying can be explained by independent variables such as Live streaming, twin dates, and social media simultaneously, while the remaining 45.6% is explained by other factors not included in this study.